2012
DOI: 10.1161/circresaha.111.255026
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Fibroblasts in Complex Fractionated Electrograms During Persistent/Permanent Atrial Fibrillation

Abstract: Rationale Electrogram-based catheter ablation, targeting complex fractionated atrial electrograms (CFAEs), is empirically known to be effective in halting persistent/permanent atrial fibrillation (AF). However, the mechanisms underlying CFAEs and electrogram-based ablation remain unclear. Objective Because atrial fibrosis is associated with persistent/permanent AF, we hypothesized that electrotonic interactions between atrial myocytes and fibroblasts play an important role in CFAE genesis and electrogram-bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
112
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 131 publications
(120 citation statements)
references
References 56 publications
7
112
0
1
Order By: Relevance
“…Combined with the timing of the action potential onset determined by the intra‐atrial signals, the in silico part calculated the virtual atrial action potentials based on the in silico model of human non‐PAF 5. Therefore, the virtual action potentials during non‐PAF could faithfully reproduce the restitution properties of human atria under structural remodeling.…”
Section: Methodsmentioning
confidence: 99%
“…Combined with the timing of the action potential onset determined by the intra‐atrial signals, the in silico part calculated the virtual atrial action potentials based on the in silico model of human non‐PAF 5. Therefore, the virtual action potentials during non‐PAF could faithfully reproduce the restitution properties of human atria under structural remodeling.…”
Section: Methodsmentioning
confidence: 99%
“…14,15 Although the importance of fibroblast-cardiomyocyte coupling in vivo is still controversial, mathematical modeling work suggests that it may account for complex fractionated electrogram properties in fibrotic tissues. 16 We have recently evaluated the effects of fibroblast ion channel remodeling on the potential electric and arrhythmogenic interactions between coupled fibroblasts and cardiomyocytes, finding that if fibroblasts were well coupled to cardiomyocytes, fibroblast Kv current downregulation would suppress the AFsubstrate, whereas Kir current upregulation would enhance it. 17 We have also obtained evidence for a profibrotic role of Kv current downregulation, although the underlying mechanism is unclear.…”
Section: Functional Role Of Ion Channels In Cardiac Fibroblastsmentioning
confidence: 99%
“…Interestingly, although focal ablation at a rotor core does not produce circuit transection and direct termination, it has been shown that focal ablation can increase the range over which a rotor core meanders. 23 This can ultimately produce rotor collision with a tissue boundary and, therefore, circuit interruption; thus, focal ablation can indirectly result in rotor annihilation.…”
Section: Ablation For Re-entrant Rhythmsmentioning
confidence: 99%